Importance of building bridging and linking social capital in adapting to changes in UK agricultural policy. (April 2021) - Arnott, David; Chadwick, David R.; Wynne-Jones, Sophie; Dandy, Norman; Jones, David L.
Abstract: As the UK leaves the European Union, the Common Agricultural Policy (CAP), which for decades has dictated how and when farming support is delivered, will be replaced with a new UK agricultural policy which will see UK farmers, especially upland livestock farmers, facing a more challenging economic environment and a significant change to the way in which farming support is delivered. This study used a series of interviews with UK farmers across differing locations and categories to ascertain how levels of social capital may hinder or enhance a farmer's willingness to embrace future agricultural policy. We found that more conventional farmers who have never participated in agri-environment schemes and those currently in government-run schemes display high levels of bonding capital and low levels of bridging and linking capital which may hinder their ability to adapt to change. In contrast, farmers who embrace a pubic goods approach to land management displayed high bridging and linking capital and are more likely to work with government officials to adapt to policy change. Communities are more likely to become sustainable if they have access to government support and advice, and if relationships with other community members and stakeholders with an interest in rural communities, the natural environment and land management are encouraged and maintained. Highlights: Conventional farmers access high levels of bonding social capital. High Nature Value Farmers access high levels of bridging and linking social capital. As farmers' community roles diminish, community co-operative action reduces. The government must shift from controller and provider to catalyst and facilitator.